Multi-Approach Integrated To Lumen Robot Friend On A Mission In For Emergency Respond - Sukoco A; Marzuki Marzuki (Bandar Lampung University (UBL), 2017)
As a social robot, a mission to find and locate objects in for evacuated of disaseter is the ability to be possessed by Lumen Robot Friend (LRF). The robot can easily become a friend and help human’s activity especially for emergency respond. Complexity in an uncertain environment from emergency, LRF is difficult to find the object that requires a scenario that involves a lot of approaches. LRF's mission is the process of completion of the mission for helping human’s activity, through the incorporation the capabilities of Face Recognition, Sign and Text recognition, gesture recognition, and object recognition of LRF in an uncertain environment, then the goals can be achieved. The focus of this research is to develop the ability to recognize the LRF, understand commands through gesture and text, search for the path based on directions, and determine a rational action and finally the object can be founded and given to the right person